Solve the linear equation: 3.4 + 2(9.7 – 4.8x) = 61.2 What are the possible steps involved in solving this equation? Check all that apply. Add 3.4 and 2. Distribute 2 to 9.7 and −4.8x. Combine 3.4 and 19.4. Divide both sides by 22.8. Subtract 22.8 from both sides. Divide both sides by −9.6.

Respuesta :

Answer:

  • Distribute 2 to 9.7 and −4.8x.
  • Combine 3.4 and 19.4.
  • Subtract 22.8 from both sides.
  • Divide both sides by −9.6

Step-by-step explanation:

Here is the recommended solution method:

  3.4 + 2(9.7 – 4.8x) = 61.2 . . . . . given

  3.4 + 19.4 - 9.6x = 61.2 . . . . . . . distribute 2 to 9.7 and -4.8x

  22.8 - 9.6x = 61.2 . . . . . . . . . . . . combine 3.4 and 19.4

  -9.6x = 38.4 . . . . . . . . . . . . . . . . . subtract 22.8 from both sides

  x = -4 . . . . . . . . . . . . . . . . . . . . . . divide both sides by -9.6

_____

Alternate solution method using different steps

You can also "undo" what is done to the variable, in reverse order. The variable has these operations performed on it:

  • multiply by -4.8
  • add 9.7
  • multiply that sum by 2
  • add 3.4 to the product

So, another possible solution method is this:

  3.4 + 2(9.7 – 4.8x) = 61.2 . . . . . given

  2(9.7 -4.8x) = 57.8 . . . . . . . . . . . add the opposite of 3.4 (undo add 3.4)

  9.7 -4.8x = 28.9 . . . . . . . . . . . . . divide by 2 (undo multiply by 2)

  -4.8x = 19.2 . . . . . . . . . . . . . . . . . add the opposite of 9.7 (undo add 9.7)

  x = -4 . . . . . . . . . . . . . . . . . . . . . . divide by -4.8 (undo multiply by -4.8)

Linear equation solutions are indeed the points where the lines or planes describing various linear equations intersect or connect. The candidate solution of a set of linear equations is indeed the collection of all feasible solution' values again for variables, and further calculation can be defined as follows:

Given:

[tex]\to \bold{3.4 + 2(9.7 -4.8x) = 61.2}\\\\[/tex]

To find:

Solve the linear equation=?

Solution:

[tex]\to \bold{3.4 + 2(9.7 -4.8x) = 61.2}\\\\\to \bold{3.4 + 19.4 -9.6x = 61.2}\\\\\to \bold{22.8 -9.6x = 61.2}\\\\\to \bold{ -9.6x = 61.2- 22.8}\\\\\to \bold{ -9.6x = 38.4}\\\\\to \bold{ x =- \frac{38.4}{9.6}}\\\\\to \bold{ x =- 4}\\\\[/tex]

Therefore, the steps are:

Distribute 2 to [tex]\bold{9.7\ and\ -4.8x}[/tex].    

Combine [tex]\bold{3.4\ and \ 19.4}[/tex].              

Subtract [tex]22.8[/tex] from both sides.      

Divide both sides by[tex]-9.6[/tex].            

Learn more:

brainly.com/question/10374924